SISTEM INFORMASI PENDATAAN OBAT MASUK PADA APOTEK HERBANA CILEGON BERBASIS WEB DENGAN MENGGUNAKAN PEMROGRAMAN CODEIGNITER - Darpi Supriyanto; Teuku Fadjar Shadek; Sawitri Nurhayati; Tiara Juliana (LPPM Unbaja, 2024)
Herbana Cilegon Pharmacy is one of the places that functions as a public health service. Seen from its function, this pharmacy functions to provide medicines that the community needs to achieve good and optimal health. Herbana Pharmacy is still done manually, employees have to record drug data in a ledger, so it takes a lot of time. The data collection process at the Cilegon Herbana Pharmacy still uses manual methods and experiences many obstacles in data processing such as data collection, calculations and making drug stock reports. Because errors in drug data collection often occur, causing inconsistencies in the amount of drug stock data recorded in the drug supply book. To overcome this problem, the author designed a system that can help in collecting data easily and can simplify the drug data collection process. To build a sales system at the Cilegon Herbana Pharmacy, the author uses use cases, class diagrams, activity diagrams, sequence diagrams, normalization and hypo, while the implementation uses PHP and MySql. The result of this research is that a web-based drug inventory information system for drug data collection is used to simplify the drug data collection process